A Prospective Analysis of Quality of Life and Toxicity Outcomes in Treating Early Breast Cancer With Breast Conservation Therapy and Intraoperative Radiation Therapy - Sosin, Michael; Gupta, Surupa Sen; Wang, Jessica S.; Costellic, Corinne D.; Gulla, Aiste; Bartholomew, Alex J.; O'Neill, Suzanne C.; Hechenbleikner, Elizabeth M.; Collins, Brian T.; Rudra, Sonali; Collins, Sean P.; Chaldekas, Krysta M.; et al. (Frontiers in Oncology, 2018)
Introduction: Intraoperative radiation therapy (IORT) is a minimally invasive radiation option for select patients with early stage breast cancer. This prospective, single institution, pilot study summarizes patient-reported quality of life (QoL) outcomes and clinician-reported toxicity following IORT following breast conservation therapy. Methods: Forty-nine patients were enrolled in a prospective study from 2013 until 2015 to assess QoL and toxicity following breast conservation therapy and IORT. Nine patients did not meet criteria for IORT alone on final pathology and required whole breast irradiation afterwards. These patients were evaluated separately. Validated QoL questionnaires were provided to patients at one-week, one-month, and subsequent six-month intervals for two years. Radiation-related toxicity symptoms were evaluated by clinicians at the same time intervals. Likert scale responses were converted to continuous variables to depict patient-reported and clinician-reported outcomes. Results: Outcomes were analyzed as weighted averages of the Likert scale for each symptom. Responses for negative QoL symptoms ranged largely from 0 (none) to 2 (moderate). Responses for positive QoL symptoms ranged largely from 3 (quite a bit) to 4 (very much). Seventy-five percent of patients developed a toxicity; however, 99% of the toxicities were grades 1 and 2. All toxicities demonstrated a downward trend over time, with the exception of breast fibrosis and nodularity, which increased over time. There were no local recurrences upon two-year follow up. Conclusion: Early stage breast cancer treated with IORT yields favorable QoL outcomes and minimal toxicity profiles with adequate short-term local control.